Amussat's Sign in Hanging – A Morphological and Histopathological Study - Maheshwari, D; Gadge , MR; Pate, RS; Bari, VB; Kennedy, A; Roy, LM (Journal of Indian Academy of Forensic Medicine, 2024)
Amussat's sign is typically a transverse laceration of the intimal layer of carotid arteries described in cases of hanging. Subtotal laceration  of the carotid artery is not strictly specific for hanging and can be also caused by blunt neck trauma, extreme overstretching, or whiplash injuries. The aim of this study is to find out the occurrence of Amussat's sign on morphological and on histopathological examination in  cases of hanging. This is an observational cross-sectional study conducted in Tertiary care hospital during time period of January 2021 –  June 2022 which consisted of 115 cases of hanging. Out of 115 cases of hanging, 93 (80.9%) cases were complete hanging. Males (n-78)  were affected more than females (n-37). The most affected age group was 21-30 years contributing to 39.1%. Most common ligature  material used was odhni (31.3%). Most common position of knot was at occipital region in 62.6% cases. Tear in carotid artery was seen in  14 (15.05%) cases on naked eye examination and all 14 cases were of complete hanging. On histopathological examination carotid intimal  tear was seen in 73.3% (n-84) cases. Amussat's sign was mostly seen in anterior hanging cases on both gross (28.6%) and histopathological  examination (85.7%). In present study Amussat's sign was present in 73.3% cases and most of them were identified by histopathological  examination rather than naked eye examination and results shows incidence of carotid tear more in complete hanging.
Keywords: Hanging; Asphyxia; Carotid intimal tear; Amussat's sign